Reported County-Level Distribution of the American Dog Tick (Acari: Ixodidae) in the Contiguous United States. Issue 1 (1st August 2019) - Lehane, Aine; Parise, Christina; Evans, Colleen; Beati, Lorenza; Nicholson, William L; Eisen, Rebecca J
Abstract: In the United States, tick-borne diseases are increasing in incidence and cases are reported over an expanding geographical area. Avoiding tick bites is a key strategy in tick-borne disease prevention, and this requires current and accurate information on where humans are at risk for exposure to ticks. Based on a review of published literature and records in the U.S. National Tick Collection and National Ecological Observatory Network databases, we compiled an updated county-level map showing the reported distribution of the American dog tick, Dermacentor variabilis (Say). We show that this vector of the bacterial agents causing Rocky Mountain spotted fever and tularemia is widely distributed, with records derived from 45 states across the contiguous United States. However, within these states, county-level records of established tick populations are limited. Relative to the range of suitable habitat for this tick, our data imply that D. variabilis is currently underreported in the peer-reviewed literature, highlighting a need for improved surveillance and documentation of existing tick records.